2021
DOI: 10.3920/jiff2020.0033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Rhodococcus rhodochrous supplementation on black soldier fly (Diptera: Stratiomyidae) development, nutrition, and waste conversion

Abstract: Black soldier fly larvae are mass produced globally for use as livestock, poultry, and aquaculture feed. Efforts are continuously seeking processes optimising larval rate of growth, size, and waste conversion as a means to lower cost and increase output. Manipulating microbes in the larval substrate (i.e. fermentation or supplementation) has been demonstrated as a potential solution. However, identifying appropriate microbes for use in this process has been limited. The objective of this study was to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…gossypii and the detoxification of toxic plant substances ( Gao et al, 2022 ). However, whether the P450 monooxygenase in Rhodococcus directly affects the metabolism of aphids is not clear ( Franks et al, 2021 ) have found that diet treatment with Rhodococcus can raise diet conversion efficiency, thus increasing body size in black soldier fly larvae. Based on these findings, we hypothesized that Rhodococcus in cotton aphid might be also responsible for biotransformation and biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…gossypii and the detoxification of toxic plant substances ( Gao et al, 2022 ). However, whether the P450 monooxygenase in Rhodococcus directly affects the metabolism of aphids is not clear ( Franks et al, 2021 ) have found that diet treatment with Rhodococcus can raise diet conversion efficiency, thus increasing body size in black soldier fly larvae. Based on these findings, we hypothesized that Rhodococcus in cotton aphid might be also responsible for biotransformation and biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…All strains exhibited cellulolytic activity tested on CMC plates. Next, oleaginous microbes, for instance Rhodococcus rhodochrous , have been opted to be of probiotic value due to their high fat content and versatile metabolism [ 40 , 41 ].…”
Section: Origin Of the Probioticsmentioning
confidence: 99%
“…1069/2009 [ 56 ]. Interestingly, feeding substrates were autoclaved in a few studies [ 41 , 43 , 47 ], probably to support colonization of the probiotics in the diets as this method would limit competition with other microorganisms. Yet, these sterilized substrates also resulted in a slower development of BSFL [ 23 , 47 , 57 ].…”
Section: Set-up Of Inoculation Trials For Bsfl Rearingmentioning
confidence: 99%
See 2 more Smart Citations